2011
DOI: 10.3109/15622975.2011.616533
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of serum BDNF: Meta-analysis of the Val66Met and genome-wide association study

Abstract: Objectives Lower levels of serum Brain Derived Neurotrophic Factor (BDNF) is one of the best known biomarkers of depression. To identify genetic variants associated with serum BDNF, we tested the Val66Met (rs6265) functional variant and conducted a genome-wide association scan (GWAS). Methods In a community-based sample (N = 2054; aged 19 to 101, M = 51, SD = 15) from Sardinia, Italy, we measured serum BDNF concentration and conducted a GWAS. Results We estimated the heritability of serum BDNF to be 0.48 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
35
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 42 publications
(51 reference statements)
8
35
4
1
Order By: Relevance
“…However, Lang et al (2009) found high BDNF serum levels in healthy Met allele subjects. The effect of an association between the BDNF Val66Met genotype and serum BDNF levels was not detected in our study, and our data agree with data from Terracciano et al (2011).…”
Section: Discussionsupporting
confidence: 83%
“…However, Lang et al (2009) found high BDNF serum levels in healthy Met allele subjects. The effect of an association between the BDNF Val66Met genotype and serum BDNF levels was not detected in our study, and our data agree with data from Terracciano et al (2011).…”
Section: Discussionsupporting
confidence: 83%
“…It will be more meaningful to detect the change of peripheral BDNF levels along with treatment response or symptom remission in longitudinal studies. We found no association between BDNF plasma levels and Val66Met polymorphism, which is consistent with other studies about BDNF levels and genetic polymorphism (Chen et al, 2014;Terracciano et al, 2013). There might be other candidate genetic polymorphism under the heritable reason for BDNF levels changing.…”
supporting
confidence: 94%
“…In sum, bearing in mind the limitations discussed in Section 4, this link seems to be valid for personality traits related to negative emotionality, as well as for psychopathology. In contrast, the meta-analysis on the link between the prominent BDNF Val66Met and BDNF serum levels [106] and between BDNF Val66Met and personality traits, such as harm avoidance/neuroticism [85], revealed no robust association. This does not mean that this association does not exist, because BDNF exerts its influence on human personality in a complicated pattern of interactions with other transmitter systems and is also modulated by the environment.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, lower hippocampus volume has been associated with higher harm avoidance and neuroticism scores in a series of studies (e.g., [4,57]), and so the 66Met allele should be indirectly associated with higher negative emotionality. Of note is a recent meta-analysis by Terracciano et al [106] showing no link between BDNF Val66Met and serum BDNF levels, therefore weakening the line of argument that the BDNF Val66Met polymorphism might be a partial cause of lower hippocampus volume due to the lower activity-dependent BDNF secretion. Clearly, BDNF levels are not only influenced by this single SNP but also from a complex mix of diverse factors, including both genetic (not only the BDNF gene) and environment factors.…”
Section: Neo-pi(-r)mentioning
confidence: 91%